Time in East Asian Endangered Languages - Grammar, History, and Society - Elia Dal Corso; Elisabetta Ragagnin; DAL CORSO, Elia; Ragagnin, Elisabetta (Edizioni Ca' Foscari, 2025)
This volume is based on a selection of papers presented at the Second Conference on the Endangered Languages of East Asia (CELEA2), hosted by the Department of Asian and North African Studies at Ca’ Foscari University of Venice on 3-5 May 2022. In each chapter, the authors discuss the topic of ‘time’ in relation to different aspects of a number of East Asian languages that are rarely represented in typological studies (Nivkh, Nighvng, Chalkan, Khitan, Ainu, Sakizaya, Kaxabu, Ryukyuan languages, Hachijō, Manchurian, and Yu). The volume will appeal to scholars with an interest in endangered languages or East Asia, and more generally will serve as a reference work in descriptive, historical and comparative linguistics, sociolinguistics, discourse studies, and lexicography.